Konsep yang Ideal tentang Pengaturan Pemilihan Kepala Daerah untuk Mewujudkan Otonomi Daerah di Indonesia - Suratin Eko Supono (Syntax Idea)
The ideal concept of setting regional head elections to realize regional autonomy in Indonesia, namely the Change in the Concept of Election of Governors of Provincial Regional Heads as Intermediary Units, is elected indirectly democratically by the Regional People's Representative Council (DPRD) on the basis of the consideration that the 4th (fourth) Pancasila precept ) Democracy Led by Wisdom in Deliberation/Representation, Article 18 paragraph (4) of the 1945 Constitution and Law Number 23 of 2014 concerning Regional Government stipulates that the Governor has a dual function, namely as the head of the provincial autonomous region and as the representative of the government center. The Governor must be seated as the representative of the central government in the regions as a deconcentration function, the Province is only tasked with coordinating the center to the regions so that it does not directly serve the needs of the community when compared to the scope of the Basic Units or Districts/Cities. The reason for the effectiveness and efficiency of the budget towards good government (good government) from a provincial perspective is that a regional area consisting of several regencies/cities requires a very large budget if the election for governors is directly elected by the people